2014
DOI: 10.4103/2229-516x.136781
|View full text |Cite
|
Sign up to set email alerts
|

Female sterilization failure: Review over a decade and its clinicopathological correlation

Abstract: Objectives:The primary objective of the following study is to determine the demographic patterns of women presenting as sterilization-failure and secondary is to evaluate possible etiological factors for failure and lay standard guidelines to reduce failure rate.Materials and Methods:The present study is retrospective study conducted in Department of Obstetrics and Gynecology, Government Medical College and Hospital-based on the case records maintained in our institution over a decade (April 2002-March 2012).R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Peterson et al 3 observed that 62% women reporting with failures were less than 28 years old and another study also quoted that 65% were below 30 years. 4 In our study, 69% women were below 30 years. Date et al 4 reported that 24.29% women presented after 20 weeks gestation and continued pregnancy, 5.71% underwent LSCS.…”
Section: Discussionmentioning
confidence: 43%
“…Peterson et al 3 observed that 62% women reporting with failures were less than 28 years old and another study also quoted that 65% were below 30 years. 4 In our study, 69% women were below 30 years. Date et al 4 reported that 24.29% women presented after 20 weeks gestation and continued pregnancy, 5.71% underwent LSCS.…”
Section: Discussionmentioning
confidence: 43%
“…As compared to similar study where <1 year interval was seen in 15% of cases and the maximal interval was 20 years. 9 In our study 29.7% patient continued their pregnancy without any future sterilization. This could be explained via the fact that that tubal occlusion could be associated with either the feeling of regret post sterilization or lack of faith in invasive permanent method after failure.…”
Section: Discussionmentioning
confidence: 47%
“…Patients should be counseled regarding failure rates depending on the timing of the procedure and the method used. The following are some of the documented reasons for tubal sterilization failure: Spontaneous recanalization Formation of tuboperitoneal fistula Selection of wrong anatomical structure (eg, round ligament, peritoneal folds)—This is an example of an operator's error Incomplete occlusion of the tube Slippage of occlusive device Pre‐existing gynecological diseases 4,6 …”
Section: Discussionmentioning
confidence: 99%